2014
DOI: 10.1149/2.1061412jes
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Mercury Electrooxidation in the Presence of Hydrogen Peroxide and Antioxidants

Abstract: The oxidation process occurring on mercury electrodes in the presence of hydrogen peroxide has been analized in basic solutions by polarography and voltammetry in their linear scan and differential pulse modes. The process involves Hg(I) ion -in addition to Hg(II) ion -and hydroperoxide radicals, these last formed at trace levels. To demonstrate this radical generation radical scavengers (antioxidants), characterized with the DPPH • radical scavenging assay, were employed. The interaction of the radicals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The structure of Eugenol allows the formation of stable radicals than the rest, because the double bound in the lateral chain and the presence of one phenolic –OH and the methoxy group. Thymol and sesamol have only one phenolic –OH, although the dioxol ring of sesamol can be opened giving relatively stable radicals (Estévez Brito et al ., ). Thus, the synergy could be related to the oxidation mechanisms and the possibility of interaction between the radicals.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The structure of Eugenol allows the formation of stable radicals than the rest, because the double bound in the lateral chain and the presence of one phenolic –OH and the methoxy group. Thymol and sesamol have only one phenolic –OH, although the dioxol ring of sesamol can be opened giving relatively stable radicals (Estévez Brito et al ., ). Thus, the synergy could be related to the oxidation mechanisms and the possibility of interaction between the radicals.…”
Section: Resultsmentioning
confidence: 97%
“…Electrochemical methods were also used, for example by monitoring the polarographic oxidation of H 2 O 2 that gives peroxide and hydroperoxide radicals (Palma et al ., ; Estévez Brito et al ., ), which interact with antioxidants (Gorjanović et al ., ). The use of the differential pulse voltammetry increased the accuracy of the measurements (Palma et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Palma et al also observed no direct reaction between AOs and peroxide itself 7 and instead hypothesized the formation of hydroperoxide radical at trace levels and its scavenging by AOs. [6][7][8] As alternative, a reaction between AOs and Hg 2+ could take place, allowing the employment of both DC polarography and DP voltammetry in AO activity measurements. Close agreement between HPMC and MRAP results indicates that the reduction leads to a decrease of Hg 2+ concentration available for…”
Section: Additivity Of Total Ao Activity Verified By Standard Additions-mentioning
confidence: 99%
“…7 Briton et al 8 also proposed a reaction of AOs with the hydroperoxide radical resulting in Hg 2+ concentration decrease and consequent decrease of the area z E-mail: stasago@yahoo.co.uk under current peak. However, the presence of radicals supposed to be formed in the range of potentials of the oxidation peak on the mercury electrode and claimed to be required to achieve the interaction with AOs as the only possibility in the system studied [6][7][8] was not confirmed. Until now, a reaction of AOs with Hg 2+ as the oxidant species capable to react was not considered, although the reduction of Hg 2+ occurring in the presence of certain phenolics and hydroquinones was reported by McKillop and Young 9 a few decades ago.…”
mentioning
confidence: 93%